The Difficulties Faced by the Fifth Semester Students of English Department of FKIP-UKI Toraja to Spell English Sound - Normalia Sirande (Jurnal Keguruan dan Ilmu Pendidikan, 2012)
The objectives of this writing are (1) to find out the difficulties faced by the fifth semester students English department of FKIP-UKI Toraja to spell English (vowel and consonant) sound, and (2) to find out what factors cause the fifth semester students English department of FKIP UKI- Toraja have difficulties to spell English (consonants and vowels) sound. This research is quantitative The population in this research was the fifth semester students of English Department of FKIP UKI Toraja. It consist of 234 students and scattered in eight classes.The research employed cluster and random sampling, where the number of the sample taken by the 1 of the eight classes (cluster sampling), but because the sample was quite big in number. So, the researcher taken the sample by using random sampling, where from the one class still random. It means that not all the students that are taken by cluster sampling as respondents. The number of the sample taken in this research as sample was 15 respondents. Based on the data and discussion it can be argued that the difficulties of the students of English Department of FKIP-UKI Toraja in spell the English (vowel and consonant) sound.The problems faced by the students arise from several factors that cause them to spell English (consonant and vowel) sound: 53.33% students difficult to differentiating the English sound, (special for the same sound [?, ð,], 40% students lazy to learn the English phonetic, 33.33 % The students less self confidence to pronounce the English phonetic, less comprehend the material, and less book in the library 26.66% The lecturer’s method not available with the material.